2009
DOI: 10.1177/1088868309339317
|View full text |Cite
|
Sign up to set email alerts
|

The Egoism and Altruism of Intergenerational Behavior

Abstract: Some of the most important issues in society today affect more than one generation of people. In this article, the authors offer a conceptual overview and integration of the research on intergenerational dilemmas-decisions that entail a tradeoff between one's own self-interest in the present and the interests of other people in the future. Intergenerational decisions are characterized by a combination of intertemporal (i.e., behaviors that affect the future) and interpersonal (i.e., behaviors that affect other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
122
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 158 publications
(202 reference statements)
5
122
0
Order By: Relevance
“…In line with this, it has been argued that equality, equity, and environmental justice are important to people due to a collective concern (Lerner, 2003;Schwartz, 1977;Tyler, 2000;Wade-Benzoni & Tost, 2009). In addition, individuals may expect to personally benefit as well when policy outcomes are distributed on the basis of equality, equity, or environmental justice, for example because people feel good about themselves when taking care of others (e.g.…”
Section: Relationship Between Fairness Acceptability and Policy Outcmentioning
confidence: 95%
See 1 more Smart Citation
“…In line with this, it has been argued that equality, equity, and environmental justice are important to people due to a collective concern (Lerner, 2003;Schwartz, 1977;Tyler, 2000;Wade-Benzoni & Tost, 2009). In addition, individuals may expect to personally benefit as well when policy outcomes are distributed on the basis of equality, equity, or environmental justice, for example because people feel good about themselves when taking care of others (e.g.…”
Section: Relationship Between Fairness Acceptability and Policy Outcmentioning
confidence: 95%
“…In addition, individuals may expect to personally benefit as well when policy outcomes are distributed on the basis of equality, equity, or environmental justice, for example because people feel good about themselves when taking care of others (e.g. Diekmann et al, 1997;Messick & McClintock, 1968;Wade-Benzoni & Tost, 2009). If people indeed care about collective outcomes, it can be expected that transport pricing policies are considered to be more fair and acceptable when policy outcomes are distributed on the basis of equality, equity, or environmental justice (i.e.…”
Section: Relationship Between Fairness Acceptability and Policy Outcmentioning
confidence: 99%
“…These types of decisions can involve a conflict between the interests of present decision-makers and the interests of future others when the decision calls for sacrifice on the part of actors in the present (Wade-Benzoni, 2002;Wade-Benzoni & Tost, 2009). For example, present generations may have to forego the consumption of desirable benefits, such as natural resources, in order to ensure the sustainability of resources for future generations.…”
Section: Introductionmentioning
confidence: 97%
“…That is, outcomes of the decision accrue not just to the self in the present but also to another person (interpersonal distance) in the future (temporal distance). Given that previous research has demonstrated that decision makers tend to discount across both of these dimensions, one would expect that the barriers to promoting intergenerational beneficence (i.e., generosity to future others) are considerable (see Wade-Benzoni & Tost, 2009, for an in-depth discussion of the barriers to intergenerational beneficence). However, previous research has uncovered a number of surprising variables that enhance intergenerational beneficence, such as outcome uncertainty (Wade-Benzoni, Hernandez, Medvec, & Messick, 2008) and mortality salience (Wade-Benzoni, Tost, Hernandez, & Larrick, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…With a few rare exceptions (e.g., Jeurissen and Keijzers 2004;Zsolnai 2006;Arenas and Rodrigo 2013), the business ethics literature has not analyzed obligations to future generations. Some scholars, coming from the field of psychology, have studied what factors elicit stewardship attitudes in managers and what psychological barriers frustrate fair decisions toward future generations (Wade-Benzoni et al 2007;Wade-Benzoni and Tost 2009;Hernandez 2012). A few articles deal with business responsibilities for child labor, child obesity, and child consumerism (Crane and Kazmi 2010;French 2010;Kolk and Van Tulder 2002).…”
Section: Introductionmentioning
confidence: 97%